A comparative investigation on the in vitro anti-inflammatory, antioxidant and antimicrobial potentials of subextracts from the aerial parts of Daphne oleoides Schreb. subsp oleoides - TAŞKIN, TURGUT (ELSEVIER SCIENCE BV, 2017)
Daphne oleoides Schreb. subsp. oleoides is an evergreen shrub which is known for its folkloric usage against various ailments such as arthritic and infectious diseases. The aim of the present study was to comparatively investigate the in vitro anti-inflammatory (nitric oxide inhibitory effects), antioxidant (DPPH center dot,ABTS(center dot+) and FRAP tests) and antimicrobial activities of the extract/subextracts from the aerial parts of D. oleoides Schreb. subsp. oleoides (Thymelaeaceae). The powdered aerial parts were first extracted with methanol and then partitioned into five subextracts (n-hexane, dichloromethane (CH2Cl2), ethyl acetate (EtOAC), n-butanol and remaining water) by succesive solvent extractions. The chemical compositions of the extracts were compared with regard to their total phenolic, total flavonoid contents and fatty acid compositions. The CH2Cl2 and n-hexane extracts exerted the highest inhibitory effect on NO production (61.67 +/- 13.97% inhibition at 50 mu g/ml and 67.91 +/- 11.17% inhibition at 100 mu g/ml, respectively) of LPS-induced Raw 264.7 cells. The EtOAC subextract showed the highest antioxidant effect evaluated by DPPH center dot (IC50: 0.35 +/- 0.12 mg/ml) and FRAP (4.54 +/- 10.01 mM FeSO4/mg extract) tests. The CH2Cl2 subextract was shown to contain the highest levels of flavonoids (0.837 +/- 10.035 mg QUE/mg extract) and was also found to be rich in phenolics (1.063 +/- 10.011 mg GAE/mg extract). Fatty acid analysis of the n-hexane extract revealed hexadecahoic acid and 9,15-octodecadienoic acids to be the major components. The n-hexane and CH2Cl2 subextracts exerted the'highest antimicrobial potential. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Daphne oleoides subsp oleoides; Anti-inflammatory; Antioxidant; Antimicrobial; Phenolics; Fatty acids; FOLK MEDICINE; TRADITIONAL MEDICINE; INFLAMMATORY RESPONSES; NATURAL ANTIOXIDANTS; GUIDED ISOLATION; NITRIC-OXIDE; PONTICA L.; FLAVONOIDS; TURKEY; CYTOKINES